Pelatihan Penulisan Karya Tulis Ilmiah Untuk Menghindari Plagiarisme Untuk Mahasiswa Semester Akhir - Fitriani, Ayu; Utari, Cut Try; Panjaitan, Joel; Syahputra, Syofyan Anwar; Pakpahan, Arnold; Sirait, Regina (Akademi Teknik Deli Serdang, 2023)
Plagiarism or often called plagiarism is plagiarism or taking other people's essays, opinions, etc. and making them look like they are your own writings and opinions. Plagiarism can be considered a criminal offense because it steals someone else's copyright. In the world of education, perpetrators of plagiarism can receive severe punishment such as expulsion from school/university. Perpetrators of plagiarism called a plagiarist. Science is developed based on previously existing knowledge. So that no one needs to hesitate when compiling a scientific work/written work, they must mention the reference source. This must be understood as intellectual honesty that will not reduce the weight of our written work. Mention honestly the reference sources we use, or make quotations, so that it will be clear which parts of our work are other people's ideas or ideas, and which are our own, this is one thing to avoid plagiarism.